The ‘caring community’: Recognizing and shielding civic environmental monitoring - Suman, Anna Berti (PINS-Psychology in Society, 2022)
‘Community-based monitoring’, is a form of care for the land, and a manifestation of broader citizen science. The practice at times embodies resistance to the way environmental resources are governed, whereas other times is a healthy complementation to institutional environmental governance. However, often, the role of such ‘monitoring’ communities is not appropriately recognized and they are even, in some instances, criminalized. Unofficial forms of monitoring should be acknowledged by institutions, especially when these institutions fail to appropriately govern environmental issues. Two cases are discussed, which – first – demonstrate the aspect of ‘care’ entailed by community-based monitoring’ and – second – the need for recognizing the added value that the civic sentinels bring to environmental governance. The main argument developed is that forms of community care for the environment should not remain an unofficial and informal practice but, when needed and as appropriate, should be recognized beyond the engaged community, mainly through the granting of a legitimate status within the system. This recognition should occur while respecting the legal context, judicial processes and the separate and unique role of authorities competent for (environmental) law enforcement.